Microscopic viscosity of neuronal plasma membranes measured using fluorescent molecular rotors: effects of oxidative stress and neuroprotection. - Kubankova,M; Summers,P; Lopez-Duarte,I; Kiryushko,D; Kuimova,MK (ACS Applied Materials and Interfaces, 2019)
Molecular mobility in neuronal plasma membranes is a crucial factor in brain function. Microscopic viscosity is an important parameter that determines molecular mobility. This study presents the first direct measurements of the microviscosity of plasma membranes of live neurons. Microviscosity maps were obtained using fluorescence lifetime imaging of environment-sensing dyes termed 'molecular rotors'. Neurons were investigated both in the basal state and following common neurodegenerative stimuli, excitotoxicity or oxidative stress. Both types of neurotoxic challenges induced microviscosity decrease in cultured neurons, and the oxidant-induced membrane fluidification was counteracted by the wide-spectrum neuroprotectant, the H3 peptide. These results provide new insights into molecular mobility in neuronal membranes, paramount for basic brain function, and suggest that preservation of membrane stability may be an important aspect of neuroprotection in brain insults and neurodegenerative disorders.